2004
DOI: 10.1038/sj.bjc.6601944
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression patterns in primary carcinoma of the vagina

Abstract: Protein patterns in six samples from primary vaginal cancers, in five from normal vaginal tissue and in five primary cervical cancers, were analysed using two-dimensional polyacrylamide gel electrophoresis (2-DE). Protein expression profile was evaluated by computer-assisted image analysis (PDQUEST) and proteins were subsequently identified using matrix-assisted laser desorption/ ionisation mass spectrometry. The aim was to analyse the protein expression profiles using the hierarchical clustering method in vag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 28 publications
2
45
0
Order By: Relevance
“…In patients suffering with cervical cancer, Hsp27 is predominantly expressed in well-differentiated SCCs and also moderately differentiated SCCs. Including our results, HSP 27 has recently been shown to be up-regulated in primary carcinoma of the vagina (11), and in C33A cells that were transfected with the HPV E7 gene (17).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In patients suffering with cervical cancer, Hsp27 is predominantly expressed in well-differentiated SCCs and also moderately differentiated SCCs. Including our results, HSP 27 has recently been shown to be up-regulated in primary carcinoma of the vagina (11), and in C33A cells that were transfected with the HPV E7 gene (17).…”
Section: Discussionmentioning
confidence: 84%
“…Proteomic and genomic approaches are now on-going to identify tumor markers. Hellman and coworkers have reported the protein expression patterns in primary carcinoma of the vagina (11).…”
Section: Introductionmentioning
confidence: 99%
“…This implies that ASF can act as an oncoprotein and that it might be a potential target for tonsillar cancer therapy [23]. Upregulation of heatshock protein 27 (HSP 27) has previously been described as a potential marker for primary carcinomas of the vagina [24]. This member of the heatshock family, which was upregulated in our tumor samples, is considered a putative biomarker for malignancy and reflects structural and metabolic disintegrity of cells.…”
Section: Discussionmentioning
confidence: 92%
“…Three 2DE studies analysing vaginal carcinoma reported over 120 proteins between them as 'different' in squamous cervical cancer tissues (Hellman et al 2004, Bae et al 2005, Zhu et al 2009); however, no biomarker panels emerged from these datasets. In another study, LCM was used to isolate high-grade, pre-cancerous cells from ThinPrep-prepared slides.…”
Section: Cervical Cancermentioning
confidence: 99%